Literary text and discourse organization modes: a semiolinguistic analyses of the fantastic short story 'Sonata', by Erico Verissmo - Moreira, Jorge de Azevedo (2020)
We present a study relating the literary fantastic genre to the discourse organization modes, according to Patrick Charaudeau's semiolinguistic theory. In line with Tzvetan Todorov, the fantastic is characterized by the hesitation effect produced in the text. It is important to study, then, how this effect becomes inserted in the narrative and descriptive organization modes. We use the short story "Sonata", by Erico Verissimo, in order to make our point.